Pengaruh Motivasi Dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada Rumah Sakit Rumah Sehat Terpadu Dompet Dhuafa Bogor - Mochammad Ichsan Ibnu Abi Muttaqien; Syahrum Agung; Mohammad Jibriel Avessina (CV. ITTC INDONESIA, 2024)
In research with the title the influence of motivation and work environment on employee performance at the puret dhuafa integred healthy hospital,Bogor, with a sample size of 78 respondents. The method used is a questionnaire research instrument distributed to employees and processed using a computer application. This research was carried out at the Bogor Dhuafa wallet integred health hospital. The variables motivation (X1) and work environment (X2) on employee performance (Y) were processed using regression analysis, t test, f test, and coefficient of determination. The results of this research show that the motivation variable (X1) and the work environment variable (X2) influence employee performance (Y) and that motivation and the work environment jointly influence employee performance.